THE EFFECT OF FIRM SIZE ON INCOME SMOOTHING WITH FINANCIAL LEVERAGE AND GOOD CORPORATE GOVERNANCE AS MODERATORS - Odilio Agung Meta Putra; Dewa Gede Wirama (Adisam Publisher, 2025)
Income smoothing is a managerial practice aimed at stabilizing reported earnings across periods. This study analyzes the effect of firm size on income smoothing with financial leverage and good corporate governance (GCG) as moderating variables in non‑financial companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. Secondary data were obtained from annual financial statements published on the official IDX website. Income smoothing is measured using the Eckel Index; firm size by the natural logarithm of total assets; financial leverage by the debt‑to‑asset ratio (DAR); and GCG by the proportion of independent commissioners. Samples were selected using Slovin’s formula and stratified random sampling, yielding 272 firms. Data were analyzed using logistic regression with moderation (Moderated Regression Analysis/MRA). The results show that firm size has a positive effect on income smoothing; financial leverage does not moderate the relationship between firm size and income smoothing; whereas GCG moderates (weakens) the effect of firm size on income smoothing.